The electronic, structural and paramagnetic properties of magnesium telluride - Akinlami, J.O.; Omeike, M.O.; Akindiilete, A.J. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2019)
This study has examined the ground-state electronic, structural, and, in addition, paramagnetic properties of semiconductor MgTe in its zinc blende phase by using the density functional theory (DFT). Exchange-correlation potentials have been approximated with the Projected Augmented Wave (PAW) Generalized Gradient Approximation (GGA). From the calculated lattice parameter, we determined the bulk modulus and first pressure derivative. Also reported are other ground state properties: density of states (DOS), band structure, projected DOS (PDOS), and magnetic properties. A direct large band-gap of 2.358 eV was observed from the band structure that has close concurrence with the previously reported values. Although this value is also smaller than the reported experimental values, it is the closest of all the calculated values. The magnetic state of the compound was observed to be paramagnetic in the ground state.